FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR MANUFAKTUR - Jennifer Alicia Widianto; Yuniarwati Yuniarwati (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
This study aims to determine whether the value of manufacturing sector companies listed on the Indonesia Stock Exchange in the 2019–2021 period is influenced by company growth, profitability, liquidity, and capital structure. All 181 manufacturing-related companies listed on the Indonesia Stock Exchange (IDX) in 2019 to 2021 constitute the study population. By method purposive sampling was used to select the sample, which includes 40 firms from the period 2019 to 2021. Multiple linear regression is the data analysis method that has been applied. According to the results of the study, company growth has no effect on firm value, profitability has an positive effect on firm value, liquidity has an positive effect on firm value, and capital structure has no effect on firm value.